2009
DOI: 10.1242/jcs.043414
|View full text |Cite
|
Sign up to set email alerts
|

Yip1A regulates the COPI-independent retrograde transport from the Golgi complex to the ER

Abstract: Yip1A, a mammalian homologue of yeast Yip1p, is a multi-spanning membrane protein that is considered to be involved in transport between the endoplasmic reticulum (ER) and the Golgi. However, the precise role of Yip1A in mammalian cells remains unclear. We show here that endogenous Yip1A is localized to the ER-Golgi intermediate compartment (ERGIC). Knockdown of Yip1A by RNAi did not induce morphological changes in the Golgi, ER, or ERGIC. By analyzing a number of intracellular transport pathways, we found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 50 publications
3
41
0
Order By: Relevance
“…The mammalian homologs (Yip1 and Yip1A) are found in the Golgi and at ER exit sites [31]. Recent studies show that Yip1A regulates the membrane association of Rab6, indicating a role in the Golgi or TGN [32]. There are seven Arabidopsis YIPs, two of which were identified in the SYP61 proteome (Supplementary information, Table S1).…”
Section: Vesicle Tethering Components Of the Syp61 Compartmentmentioning
confidence: 99%
“…The mammalian homologs (Yip1 and Yip1A) are found in the Golgi and at ER exit sites [31]. Recent studies show that Yip1A regulates the membrane association of Rab6, indicating a role in the Golgi or TGN [32]. There are seven Arabidopsis YIPs, two of which were identified in the SYP61 proteome (Supplementary information, Table S1).…”
Section: Vesicle Tethering Components Of the Syp61 Compartmentmentioning
confidence: 99%
“…Proteins of the YIP family are found in all eukaryotic organisms but have been studied most extensively in yeast and, more recently, in mammals. YIPs play a crucial role in vesicle trafficking (Yang et al, 1998;Matern et al, 2000;Barrowman et al, 2003;Heidtman et al, 2003;Chen et al, 2004;Collins, 2005b, 2005a;Yoshida et al, 2008;Kano et al, 2009;Tanimoto et al, 2011), which may involve their ability to bind RAB GTPases (RABs; hence their name Ypt/Rab Interacting Protein) (Yang et al, 1998), making them attractive candidates for the recruitment of RABs onto target membranes (Yang et al, 1998;Barrowman et al, 2003;Calero et al, 2003;Heidtman et al, 2003;Chen et al, 2004). YIP1p, the best characterized member of the yeast YIP family, acts in the secretory pathway at an early stage (Yang et al, 1998;Matern et al, 2000;Calero et al, 2003), but it remains unclear whether YIP1p regulates vesicle fusion at the Golgi apparatus (Barrowman et al, 2003) or vesicle budding from the endoplasmic reticulum (ER) (Heidtman et al, 2003).…”
Section: Ech/yip4a/yip4b Is a Conserved Eukaryotic Interactionmentioning
confidence: 99%
“…It is also possible that there is an effect on the anterograde or retrograde transport of some proteins, which was not detectable in our experiments. It has been shown that the knockdown of YIPF5/YIP1A causes a reduction in COPI independent Golgi to ER retrograde transport (Kano et al, 2009). Therefore, it is possible that YIPF3 and YIPF4 also function in Golgi to ER retrograde transport.…”
Section: Functions Of Yipf3 and Yipf4mentioning
confidence: 99%
“…However, the knockdown of YIPF5 or YIF1A does not affect anterograde transport of transmembrane or soluble marker proteins while it causes significant fragmentation of the Golgi apparatus (Yoshida et al, 2008). In addition, it has recently been shown that the knock down of YIPF5 (Yip1A) causes delay in the Golgi to the ER retrograde transport of COPI independent cargo molecules while not affecting the anterograde transport and COPI dependent Golgi to ER retrograde transport pathway (Kano et al, 2009). Therefore, whether YIPF5 (Yip1A) functions in anterograde transport remains uncertain.…”
Section: Introductionmentioning
confidence: 99%